The Modification of Plant Cell Wall Polysaccharides in Potato Plants during Pectobacterium atrosepticum-Caused Infection - Vladimir Gorshkov; Ivan Tsers; Bakhtiyar Islamov; Marina Ageeva; Natalia Gogoleva; Polina Mikshina; Olga Parfirova; Olga Gogoleva; Olga Petrova; Tatyana Gorshkova; Yuri Gogolev (Plants, 2021)
Our study is the first to consider the changes in the entire set of matrix plant cell wall (PCW) polysaccharides in the course of a plant infectious disease. We compared the molecular weight distribution, monosaccharide content, and the epitope distribution of pectic compounds and cross-linking glycans in non-infected potato plants and plants infected with Pectobacterium atrosepticum at the initial and advanced stages of plant colonization by the pathogen. To predict the gene products involved in the modification of the PCW polysaccharide skeleton during the infection, the expression profiles of potato and P. atrosepticum PCW-related genes were analyzed by RNA-Seq along with phylogenetic analysis. The assemblage of P. atrosepticum biofilm-like structures—the bacterial emboli—and the accumulation of specific fragments of pectic compounds that prime the formation of these structures were demonstrated within potato plants (a natural host of P. atrosepticum). Collenchyma was shown to be the most “vulnerable” tissue to P. atrosepticum among the potato stem tissues. The infection caused by the representative of the Soft Rot Pectobacteriaceae was shown to affect not only pectic compounds but also cross-linking glycans; the content of the latter was increased in the infected plants compared to the non-infected ones.